Identification of acid-fast bacteria in sputum samples using the kinyoun gabbet staining method - Evi Damayanti (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2023)
Pulmonary tuberculosis is an acute and chronic infectious disease that mainly attacks the lungs, caused by rod-resistant bacteria (BTA) that are Gram Positive (mycobacterium tuberculosis). The diagnosis of pulmonary tuberculosis in adults can be established by finding BTA on microscopic examination of the sputum. This study is descriptive to find mycobacterium tuberculosis germs in sputum patients with clinical diagnosis of tuberculosis in general poly. BTA coloring technique using Kinyoun Gabbet method. The results showed that from 10 samples, 3 samples were positive (+) and 7 samples were negative. Positive BTA sputum tests are fewer than negative BTA